The Karakteristik Endapan di Sekitar Kali Serang Kulon Progo, Yogyakarta - Winarti, Winarti (ReTII, 2022)
The Serang watershed includes the main river (Kali Serang) and its tributaries, which flow into the Indian Ocean from the Menoreh Hills and estuary. The Serang River downstream has a flat topography and has the potential to be developed as a tourist destination. Furthermore, it is ideal for the development of public service facilities. Sediment deposits (alluvium) of gravel, sand, silt, and sand surround the Serang River. Clay and fine sand are the most common deposits. The purpose of the study was to determine the type of sediment surrounding the Serang River downstream and whether it was expansive or not. A hand borehole was used to collect sediment samples at a depth of 4 meters. The X-Ray Diffraction (XRD) method for sample analysis The sediment was dark brown to black in color, wet, not compacted, sticky, and sized with clay mixed with fine sand and large foraminifera shells, as per megascopic observations. XRD analysis with glycol oriented revealed the presence of Nantronit-15A and Nakrite-2 clay types. The presence of Nantronit-15A is greater than Nakrit-2. Nantronite-15A is a part of the smectite (montmorillonite) group, which can absorb water and has a high swelling-shrinkage proportion (expansive). Nakrit-2 has a monoclinic crystal system, is a part of the kaolinite group, and has a low swelling-shrink capacity (not expansive). Because the distribution of Nantronite-15A is greater than that of Nakrit-2, the sample has a more expansive character. Extensive deposits will be at risk if a building is constructed. As a consequence, efforts must be made to enhance (stabilize) the soil.